Alanine-aminotransferase levels predict impaired glucose tolerance in a worksite population - Oberlinner, Christoph; Zober, Andreas; Nawroth, Peter Paul; Humpert, Per Magnus; Morcos, Michael (Acta diabetologica, 2010)
Insulin resistance and impaired glucose tolerance precede the development of type 2 diabetes. In 2006, the BASF Occupational Medicine and Health Protection Department offered a diabetes screening program for 33,000 employees. 1,594 employees had their diabetes risk tested: 285 employees were at medium to high risk for diabetes type 2, according to the Finrisk score. Hundred and fifty-seven of these individuals underwent oral glucose tolerance testing: 22 were shown to have impaired glucose tolerance (IGT), and 5 had manifest diabetes. Thus, 18% of this worksite sample population were affected by IGT or type 2 diabetes. A total of 87% were affected by metabolic syndrome (MS) according to the International Diabetes Federation (IDF) criteria. At baseline, individuals with normal glucose tolerance and impaired glucose tolerance differed significantly with respect to fasting glucose (97 ± 8 vs. 103 ± 10 mg/dl, P < 0.01), HbA1c (5.5 ± 0.3 vs. 5.7 ± 0.4%, P < 0.01), and alanine-aminotransferase (ALT) (28 ± 15 vs. 36 ± 18 U/I, P < 0.05). In binary logistic regression analysis adjusted for age and gender, fasting glucose and ALT were the only independent predictors of impaired glucose tolerance (OR 4.8 [1.24-24.8] and OR 5.5 [1.2-24.8]), while age and HbA1c had only borderline significance (OR 3.9 [0.94-15.92] and OR 2.8 [0.94-8.67]). Waist circumference, BMI, triglycerides, and HDL as central components of the MS had no predictive value for impaired glucose tolerance. In summary, in this particular sample population, fasting glucose and ALT were the only significant predictors of IGT. These data point to an important role of the liver in insulin resistance and the development of impaired glucose tolerance in the relatively young and small population studied.